An investigation of the performance of NiTi shape memory alloy based bone fixation device - Yong, Thian Haw (2015)
This project has involved design of a new bone fixation device made of NiTi shape memory alloy. Conceptual designs were generated by using Product Design Specification (PDS) and brainstorming methods. The concept evaluation of the conceptual designs has been carried out by means of weighted objective method and the conceptual design that scores highest was chosen as the best design concept. The concept of Nitinol Stitch was the most suitable for bone fixation device because of large size of fracture coverage and excellent adaptability to bone geometry when compared to other design concepts. The new bone fixation device model was fabricated by using NiTi shape memory alloy as its main constituent. Performance of the newly designed bone fixation device model made of NiTi shape memory alloy was evaluated. Meanwhile, commercial finite element analysis (FEA) software, Abaqus was used to analyze the mechanics of model as well as its behavior, so that the installation process during orthopedic surgery can be simulated. A prototype has been fabricated. Heat test was conducted in laboratory to investigate the actual performance of the prototype. Experimental data were compared to the simulation data for result validation. From simulation, it is found that the gap between two bone fragments has been reduced from 2mm to 0.2mm. However, slipping occurred during experiment, the gap has increased up to 6.54mm. The simulation result was further explored to justify the device’s feasibility. The findings of this research will provide one of the possibilities that can be made to solve shortcomings of a few existing SMA based bone fixation devices as reviewed in literature. The research has led to a conclusion that the newly designed device, Nitinol Stitch, has shown its potential advantages in orthopedics by offering a new alternative in fixing bone fracture. The design and experimental processes throughout the project can be used as a reference for future development of other SMA based bone fixation devices.